Традиции и новаторство в творчестве Д. Бедного - Бакина, М.А. (Kalbotyra, 1985)
The means of using traditional poetic images by D. Bedny are discussed. The author puts forward the thesis of specific utilization of these images by the poet being closely connected with the themes of his works as well as with the genre orientation.